Group project practices and guidance in higher education contexts - Wang, Zhihan; Gupta, Sejal; Page, Freddie; Agg, Chloe; Spivey, Alan C.; Hazeri, Kamyar; Zou, Yixin; Zhao, Chao; Lucas, Claire; Childs, Peter R. N. (Frontiers in Education, 2025)
Anecdotal good practice in group projects is widely available. In the academic context group project work offers potential for real world experience development along with enabling activities to be undertaken within limited resources. Nevertheless, concerns exist regarding aspects such as fairness, burden and unpopularity. This paper provides a review of commonly cited best practice for group projects, supplemented by a cross-university review undertaken by students of group projects at Imperial in combination with guidance from three other universities. Arising highlighted good practice principles include prioritization, holding a kick-off meeting, establishment of project scope and objectives, attention to group composition, resource planning, change management, project planning, risk management, documentation, communication, cooperation, culture and psychological safety, dependability, sense of purpose, conflict management and feedback. From the extensive body of guidance available it is evident that we could learn more from industrial approaches to project management. However, it is also acknowledged that maximizing outcomes may not maximize learning, especially for academically weaker and stronger students. A recommendation arising from practice in some modules and industry includes ongoing attention to project management training and role development during a project so that practitioners can continue to learn and upskill within a project and specific role, rather than relying on training sessions before a project.